2008
DOI: 10.4049/jimmunol.181.2.1420
|View full text |Cite
|
Sign up to set email alerts
|

Malaria-Specific and Nonspecific Activation of CD8+ T Cells during Blood Stage of Plasmodium berghei Infection

Abstract: Cerebral malaria is one of the severe complications of Plasmodium falciparum infection. Studies using a rodent model of Plasmodium berghei ANKA infection established that CD8+ T cells are involved in the pathogenesis of cerebral malaria. However, it is unclear whether and how Plasmodium-specific CD8+ T cells can be activated during the erythrocyte stage of malaria infection. We generated recombinant Plasmodium berghei ANKA expressing OVA (OVA-PbA) to investigate the parasite-specific T cell responses during ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
80
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 48 publications
8
80
0
Order By: Relevance
“…1) : depletion of CD8 + T cells either early (from start of infection) or late (from day 4 or 5 post-infection) in infection completely inhibits the development of ECM (Yanez et al 1996 ;Belnoue et al 2002 ;Hermsen et al 1997). CD8 + T cells migrate to the brain in a largely antigen-specific manner, following cross-presentation of malaria antigens by classical CD8 + dendritic cells (deWalick et al 2007 ;Lundie et al 2008 ;Miyakoda et al 2008). The recent demonstration that NK cell-derived IFN-c is required for upregulation of CXCR3 on CD8 + T cells and for their subsequent migration to and accumulation within the brain ) is consistent with the observation that IFN-cR signalling regulates sequestration of CD8 + T cells within the brain in susceptible mice (Belnoue et al 2008), and reveals important interactions between innate and adaptive immune responses in the pathogenesis of ECM, opening up potential new avenues of research into the role of innate immune responses, and of genetic variation in innate response genes, in the pathogenesis of human CM.…”
Section: Experimental Cerebral Malariamentioning
confidence: 99%
“…1) : depletion of CD8 + T cells either early (from start of infection) or late (from day 4 or 5 post-infection) in infection completely inhibits the development of ECM (Yanez et al 1996 ;Belnoue et al 2002 ;Hermsen et al 1997). CD8 + T cells migrate to the brain in a largely antigen-specific manner, following cross-presentation of malaria antigens by classical CD8 + dendritic cells (deWalick et al 2007 ;Lundie et al 2008 ;Miyakoda et al 2008). The recent demonstration that NK cell-derived IFN-c is required for upregulation of CXCR3 on CD8 + T cells and for their subsequent migration to and accumulation within the brain ) is consistent with the observation that IFN-cR signalling regulates sequestration of CD8 + T cells within the brain in susceptible mice (Belnoue et al 2008), and reveals important interactions between innate and adaptive immune responses in the pathogenesis of ECM, opening up potential new avenues of research into the role of innate immune responses, and of genetic variation in innate response genes, in the pathogenesis of human CM.…”
Section: Experimental Cerebral Malariamentioning
confidence: 99%
“…Very recently, a few groups demonstrated the expansion of CD4 and CD8 T cells during the blood stage of malaria, but these studies did not address the expression, stability and fidelity of the above-mentioned markers during infection. 12,30,31 The purpose of this study was to evaluate the extent, quality and quantity of CD8 and CD4 T-cell activation after blood-stage malaria infection that did not involve a liver stage. We found that both CD8 and CD4 T cells These data clearly demonstrate that CD8 and CD4 T cells are activated following an acute blood-stage malaria infection.…”
Section: M M U N O L O G Y O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…The lack of TCR transgenic mouse lines specific for Plasmodium Ags led to the generation of transgenic malaria parasites expressing model Ags, such as PbTG and OVA-Plasmodium berghei ANKA (PbA) (2,4,9,10), for which widely used murine T cell lines such as OT-I and OT-II could be used to monitor specific T cell responses. Although the use of these parasites in conjunction with model T cell lines has aided the study of antimalarial CD4 + and CD8 + T cell responses (6,(11)(12)(13)(14)(15), wild-type (WT) parasites and transgenic T cells capable of recognizing authentic parasitederived Ags are preferred, as they more closely resemble endogenous responses to natural infections.…”
mentioning
confidence: 99%